Safety and tolerability of fixed antihypertensive combinations in blood pressure control: focus on olmesartan medoxomil and amlodipine combination - Ijlal Uddin; Shakil Aslam (Dove Medical Press, 2010)
Ijlal Uddin, Shakil AslamDivision of Nephrology and Hypertension, Georgetown University Hospital, Washington, District of Columbia, USAAbstract: Hypertension is a major health problem worldwide and remains underdiagnosed and undertreated. Although public awareness and control of hypertension have improved over the last decade, only one-third of hypertensive patients achieve the rather conservative blood pressure (BP) goal of <140/90 mmHg. Most hypertensive patients require more than one drug for optimum BP control. Expert panels recommend use of combination therapy with two or more medications for Stage 2 and higher hypertension and in high-risk patients. However, the use of multiple drugs reduces patient compliance. Fixed-dose combination therapy helps improve patient compliance and thus achieve the target BP. Dose titration of the individual constituent drugs is recommended before switching to an equivalent fixed-dose combination. Randomized, controlled trials have shown that the fixed-dose combination of amlodipine–olmesartan medoxomil is more effective in lowering BP than monotherapy with either of these agents, with a similar side effect profile.Keywords: hypertension, target blood pressure, compliance, amlodipine, olmesartan